Nanoemulsion of Amber rice bran oil (Oryza sativa L.), characterization and properties - Turki, Saif Saad; Mohammed, Nameer Kh.; Muhialdin, Belal J.; Hussin, Anis S. (Tikrit University, 2024)
A nanoemulsion of Iraqi Amber rice bran oil (NARBO) was prepared using an ultrasonic method. The nanoemulsions: NE1, NE2, and NE3 were formulated using an emulsifier (Tween 80 and sodium caseinate) in a ratio of 1:1 and at a concentration of (1.5, 2, 2.5%), and were examined to ensure their stability and physicochemical properties. All nanoemulsions carried a negative charge for zeta potential ranging between-31.51 and-18.52, with the highest value recorded in NE1 on day 7. The negative zeta potential increased on day 7 for all prepared nanoemulsions. and concerning droplet size, it ranged (from 89.4 to 144.2 nm), and the smallest size was recorded in NE3. Increasing the emulsifier concentration resulted in decreased droplet sizes. All nanoemulsions had good droplet size distribution, with a Polydispersity Index of less than 0.3. FE-SEM images revealed that the nanoemulsion droplets were spherical, uniformly distributed, and well-coated at all emulsifier concentrations. Viscosity values ranged between (3.5 to 6.2 cP) and increased with the concentration of emulsifier. From the results of the stability test, it can be concluded that NE3 was the most stable during the period studied, as the lipid index (CI) remained zero until the seventh day. The highest value of oil encapsulation efficiency (EE) (97.60%) was recorded in NE3. These results showed that a stable nanoemulsion was successfully prepared from Iraqi amber rice bran oil, which could represent a promising solution for improving the stability and bioavailability of the oil and the active and effective compounds it contains.